Homing navigation is optimized to diurnal constraints in a tropical seabird, the red-footed booby - Joshua Coste; Stephen C. Votier; Ruth E. Dunn; Robin Freeman; Malcolm A. Nicoll; Peter Carr; Hannah Wood; Alice M. Trevail (Animal Behaviour, 2025)

The importance of locally sourced data in identifying population trends: Insights from Iberian vertebrates - Roberto C. Rodríguez-Caro; Zebensui Morales-Reyes; Alba Aguión; Rebeca Arias-Real; Eneko Arrondo; Eneko Aspillaga; Jordi Boada; Andrea Campos-Candela; Mónica Expósito-Granados; Aitor Forcada; Robin Freeman; Miguel Ángel Gómez-Serrano; et al. (Biological Conservation, 2024)

Comparable foraging effort and habitat use between two geographically proximate tropical seabird colonies - Alice M. Trevail; Sonia Vallocchia; Malcolm A. C. Nicoll; Peter Carr; Stephen C. Votier; Hannah Wood; Robin Freeman (Marine Biology, 2024)
Effective seabird conservation requires understanding their marine spatial ecology. Tracking can reveal details of their foraging ecology and habitat use, as well as the suitability of marine protected areas for at-sea conservation, but results are often regionally specific. Here we characterised the foraging behaviour of tropical breeding brown boobies Sula leucogaster in the Chagos Archipelago, Western Indian Ocean, and tested habitat requirements. GPS tracking of thirteen individuals from two colonies, located 142 km apart on the same atoll (Great Chagos Bank), showed similar foraging effort and habitat preferences despite differences in season and breeding stage. Brown boobies from both tracked populations foraged close to the colony along the atoll shelf edge, avoiding deep oceanic areas and shallow waters of the Great Chagos Bank atoll, but within the Chagos Archipelago Marine Protected Area. Sea-level height anomaly and sea surface temperature were important foraging predictors at both sites, although birds experienced distinct environmental conditions between colonies. These results suggest that while brown boobies have colony-specific at-sea foraging areas, similarities in habitat drivers of distribution and foraging behaviour can inform predictions of distributions at other colonies within the archipelago, with important benefits for at-sea conservation efforts.

From route to dive: multi-scale habitat selection in a foraging tropical seabird - Ruth E. Dunn; Robin Freeman; Malcolm A. Nicoll; Julia Ramsden; Alice M. Trevail; Hannah Wood; Stephen C. Votier (Marine Biology, 2024)
Comprehending how environmental variability shapes foraging behaviour across habitats is key to unlocking insights into consumer ecology. Seabirds breeding at high latitudes are exemplars of how marine consumers can adapt their behaviours to make use of predictable foraging opportunities, but prey tends to be less predictable in tropical oceanic ecosystems and may require alternative foraging behaviours. Here we used GPS and time-depth recorder loggers to investigate the foraging behaviour of central placed adult red-footed boobies ( Sula sula rubripes ), a tropical seabird that forages in oceanic waters via diving, or by capturing aerial prey such as flying fish in flight. Dive bout dynamics revealed that red-footed boobies appeared to exploit denser, but more sparsely distributed prey patches when diving further from the colony. Furthermore, although we found no evidence of environmentally driven habitat selection along their foraging routes, red-footed boobies preferentially dived in areas with higher sea surface temperatures and chlorophyll-a concentrations compared to conditions along their foraging tracks. This multi-scale variation implies that habitat selection differs between foraging routes compared to dive locations. Finally, red-footed booby dives were deepest during the middle of the day when light penetration was greatest. Ultimately, we highlight the importance of gaining insights into consumer foraging across different ecosystems, thereby broadening understanding of how animals might respond to changing environmental conditions.

Quantifying reliability and data deficiency in global vertebrate population trends using the Living Planet Index - Shawn Dove; Monika Böhm; Robin Freeman; Louise McRae; David J. Murrell (Global Change Biology, 2023)
Global biodiversity is facing a crisis, which must be solved through effective policies and on‐the‐ground conservation. But governments, NGOs, and scientists need reliable indicators to guide research, conservation actions, and policy decisions. Developing reliable indicators is challenging because the data underlying those tools is incomplete and biased. For example, the Living Planet Index tracks the changing status of global vertebrate biodiversity, but taxonomic, geographic and temporal gaps and biases are present in the aggregated data used to calculate trends. However, without a basis for real‐world comparison, there is no way to directly assess an indicator's accuracy or reliability. Instead, a modelling approach can be used. We developed a model of trend reliability, using simulated datasets as stand‐ins for the “real world”, degraded samples as stand‐ins for indicator datasets (e.g., the Living Planet Database), and a distance measure to quantify reliability by comparing partially sampled to fully sampled trends. The model revealed that the proportion of species represented in the database is not always indicative of trend reliability. Important factors are the number and length of time series, as well as their mean growth rates and variance in their growth rates, both within and between time series. We found that many trends in the Living Planet Index need more data to be considered reliable, particularly trends across the global south. In general, bird trends are the most reliable, while reptile and amphibian trends are most in need of additional data. We simulated three different solutions for reducing data deficiency, and found that collating existing data (where available) is the most efficient way to improve trend reliability, whereas revisiting previously studied populations is a quick and efficient way to improve trend reliability until new long‐term studies can be completed and made available.

Achieving a real‐time online monitoring system for conservation culturomics - Thomas Frederick Johnson; Richard Cornford; Shawn Dove; Robin Freeman; Joseph Millard (Conservation Biology, 2023)
Environmental monitoring is increasingly shifting toward a set of systems that describe changes in real time. In ecology specifically, a series of challenges have prevented the rollout of real‐time monitoring for features such as biodiversity change or ecosystem service provision. Conservation culturomics, a field concerned with interactions between people and nature, is well placed to demonstrate how monitoring might move toward a network of real‐time platforms, given its existence exclusively in the digital realm. We examined a set of considerations associated with the development of real‐time monitoring platforms for conservation culturomics and introduce a near real‐time platform for the Species Awareness Index, a global index of changing biodiversity awareness derived from the rate of change in page views for species on Wikipedia. This platform will update automatically each month, operating in near real time ( https://joemillard.shinyapps.io/Real_time_SAI/ ). There are plans to make the underlying data queryable via an application programing interface independent of the platform. The real‐time Species Awareness Index will represent the first real‐time and entirely automated conservation culturomic platform and one of the first real‐time platforms in the discipline of ecology. Real‐time monitoring for culturomics can provide insight into human–nature interactions as they play out in the physical realm and provide a framework for the development of real‐time monitoring in ecology. Real‐time monitoring metrics can be processed on private virtual machines and hosted on publicly available cloud services. Conservation now needs an online, real‐time observatory that can evolve with the structure of the web.

Monitoring extinction risk and threats of the world’s fishes based on the Sampled Red List Index - Rafael Miranda; Imanol Miqueleiz; William Darwall; Catherine Sayer; Nicholas K. Dulvy; Kent E. Carpenter; Beth Polidoro; Nadia Dewhurst-Richman; Caroline Pollock; Craig Hilton-Taylor; Robin Freeman; Ben Collen; et al. (Reviews in Fish Biology and Fisheries, 2022)
Global biodiversitytargets require us to identify species at risk of extinction and quantify status and trends of biodiversity. The Red List Index (RLI) tracks trends in the conservation status of entire species groups over time by monitoring changes in categories assigned to species. Here, we calculate this index for the world’s fishes in 2010, using a sampled approach to the RLI based on a randomly selected sample of 1,500 species, and also present RLI splits for freshwater and marine systems separately. We further compare specific traits of a worldwide fish list to our sample to assess its representativeness. Overall, 15.1% of species in the sample were estimated to be threatened with extinction, resulting in a sampled RLI of 0.914 for all species, 0.968 in marine and 0.862 in freshwater ecosystems. Our sample showed fishing as the principal threat for marine species, and pollution by agricultural and forestry effluents for freshwater fishes. The sampled list provides a robust representation for tracking trends in the conservation status of the world’s fishes, including disaggregated sampled indices for marine and freshwater fish. Reassessment and backcasting of this index is urgent to check the achievement of the commitments proposed in global biodiversity targets.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Vertebrate population trends are influenced by interactions between land use, climatic position, habitat loss and climate change - Jessica J. Williams; Robin Freeman; Fiona Spooner; Tim Newbold (Global Change Biology, 2022)
Rapid human‐driven environmental changes are impacting animal populations around the world. Currently, land‐use and climate change are two of the biggest pressures facing biodiversity. However, studies investigating the impacts of these pressures on population trends often do not consider potential interactions between climate and land‐use change. Further, a population's climatic position (how close the ambient temperature and precipitation conditions are to the species’ climatic tolerance limits) is known to influence responses to climate change but has yet to be investigated with regard to its influence on land‐use change responses over time. Consequently, important variations across species’ ranges in responses to environmental changes may be being overlooked. Here, we combine data from the Living Planet and BioTIME databases to carry out a global analysis exploring the impacts of land use, habitat loss, climatic position, climate change and the interactions between these variables, on vertebrate population trends. By bringing these datasets together, we analyse over 7,000 populations across 42 countries. We find that land‐use change is interacting with climate change and a population's climatic position to influence rates of population change. Moreover, features of a population's local landscape (such as surrounding land cover) play important roles in these interactions. For example, populations in agricultural land uses where maximum temperatures were closer to their hot thermal limit, declined at faster rates when there had also been rapid losses in surrounding semi‐natural habitat. The complex interactions between these variables on populations highlight the importance of taking intraspecific variation and interactions between local and global pressures into account. Understanding how drivers of change are interacting and impacting populations, and how this varies spatially, is critical if we are to identify populations at risk, predict species’ responses to future environmental changes and produce suitable conservation strategies.

Global patterns of resilience decline in vertebrate populations - Pol Capdevila; Nicola Noviello; Louise McRae; Robin Freeman; Christopher F. Clements (Ecology Letters, 2022)
Maintaining the resilience of natural populations, their ability to resist and recover from disturbance, is crucial to prevent biodiversity loss. However, the lack of appropriate data and quantitative tools has hampered our understanding of the factors determining resilience on a global scale. Here, we quantified the temporal trends of two key components of resilience—resistance and recovery—in >2000 population time‐series of >1000 vertebrate species globally. We show that the number of threats to which a population is exposed is the main driver of resilience decline in vertebrate populations. Such declines are driven by a non‐uniform loss of different components of resilience (i.e. resistance and recovery). Increased anthropogenic threats accelerating resilience loss through a decline in the recovery ability—but not resistance—of vertebrate populations. These findings suggest we may be underestimating the impacts of global change, highlighting the need to account for the multiple components of resilience in global biodiversity assessments.

The species awareness index as a conservation culturomics metric for public biodiversity awareness - Joseph W. Millard; Richard D. Gregory; Kate E. Jones; Robin Freeman (Conservation Biology, 2021)
Although threats to global biodiversity are well known, slowing current rates of biodiversity loss remains a challenge. The Aichi targets set out 20 goals on which the international community should act to alleviate biodiversity decline, 1 of which (Target 1) aims to raise public awareness of the importance of biodiversity. Although conventional indicators for Target 1 are of low spatial and temporal coverage, conservation culturomics metrics show how biodiversity awareness can be quantified at the global scale. Following methods used for the Living Planet Index, we devised a species awareness index (SAI) to measure change in species awareness based on Wikipedia views. We calculated this index at the page level for 41,197 species listed by the International Union for Conservation of Nature (IUCN) across 10 Wikipedia languages and >2 billion views from 1 July 2015 to 30 March 2020. Bootstrapped indices for the page‐level SAI showed that overall awareness of biodiversity increased marginally over time, although there were differences among taxonomic classes and languages. Among taxonomic classes, overall awareness increased fastest for reptiles and slowest for amphibians. Among languages, overall species awareness increased fastest for Japanese and slowest for Chinese and German users. Although awareness of species as a whole increased and was significantly higher for traded species, from January 2016 through January 2020, change in awareness appeared not to be strongly related to whether the species is traded or is a pollinator. As a data source for public biodiversity awareness, the SAI could be integrated into the Conservation International Biodiversity Engagement Indicator.

Fast, scalable, and automated identification of articles for biodiversity and macroecological datasets - Richard Cornford; Stefanie Deinet; Adriana De Palma; Samantha L. L. Hill; Louise McRae; Benjamin Pettit; Valentina Marconi; Andy Purvis; Robin Freeman (Global Ecology and Biogeography, 2021)
Aim Understanding broad‐scale ecological patterns and processes is necessary if we are to mitigate the consequences of anthropogenically driven biodiversity degradation. However, such analyses require large datasets and current data collation methods can be slow, involving extensive human input. Given rapid and ever‐increasing rates of scientific publication, manually identifying data sources among hundreds of thousands of articles is a significant challenge, which can create a bottleneck in the generation of ecological databases. Innovation Here, we demonstrate the use of general, text‐classification approaches to identify relevant biodiversity articles. We apply this to two freely available example databases, the Living Planet Database and the database of the PREDICTS (Projecting Responses of Ecological Diversity in Changing Terrestrial Systems) project, both of which underpin important biodiversity indicators. We assess machine‐learning classifiers based on logistic regression (LR) and convolutional neural networks, and identify aspects of the text‐processing workflow that influence classification performance. Main conclusions Our best classifiers can distinguish relevant from non‐relevant articles with over 90% accuracy. Using readily available abstracts and titles or abstracts alone produces significantly better results than using titles alone. LR and neural network models performed similarly. Crucially, we show that deploying such models on real‐world search results can significantly increase the rate at which potentially relevant papers are recovered compared to a current manual protocol. Furthermore, our results indicate that, given a modest initial sample of 100 relevant papers, high‐performing classifiers could be generated quickly through iteratively updating the training texts based on targeted literature searches. These findings clearly demonstrate the usefulness of text‐mining methods for constructing and enhancing ecological datasets, and wider application of these techniques has the potential to benefit large‐scale analyses more broadly. We provide source code and examples that can be used to create new classifiers for other datasets.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Working along the Continuum: North Carolina’s Collaborative Response to COVID-19 for Migrant & Seasonal Farmworkers - Robin Tutor Marcom; Elizabeth Freeman Lambar; Beth Rodman; Gayle Thomas; Ann Watson; Bryan Parrish; Jessica Wilburn (Journal of Agromedicine, 2020)

Mammalian tolerance to humans is predicted by body mass: evidence from long‐term archives - Jennifer J. Crees; Samuel T. Turvey; Robin Freeman; Chris Carbone (Ecology, 2019)
Humans are implicated as a major driver of species extinctions from the Late Pleistocene to the present. However, our predictive understanding of human‐caused extinction remains poor due to the restricted temporal and spatial scales at which this process is typically assessed, and the risks of bias due to “extinction filters” resulting from a poor understanding of past species declines. We develop a novel continent‐wide data set containing country‐level last‐occurrence records for 31 European terrestrial mammals across the Holocene (c.11,500 yr BP to present), an epoch of relative climatic stability that captures major transitions in human demography. We analyze regional extirpations against a high‐resolution database of human population density ( HPD ) estimates to identify species‐specific tolerances to changing HPD through the Holocene. Mammalian thresholds to HPD scale strongly with body mass, with larger‐bodied mammals experiencing regional population losses at lower HPD s than smaller‐bodied mammals. Our analysis enables us to identify levels of tolerance to HPD for different species, and therefore has wide applicability for determining biotic vulnerability to human impacts. This ecological pattern is confirmed across wide spatiotemporal scales, providing insights into the dynamics of prehistoric extinctions and the modern biodiversity crisis, and emphasizing the role of long‐term archives in understanding human‐caused biodiversity loss.

The buzz segment of Savannah sparrow song is a population marker - Heather Williams; Clint W. Robins; D. Ryan Norris; Amy E. M. Newman; Corey R. Freeman-Gallant; Nathaniel T. Wheelwright; Daniel J. Mennill (Journal of Ornithology, 2019)

Rapid warming is associated with population decline among terrestrial birds and mammals globally - Fiona E. B. Spooner; Richard G. Pearson; Robin Freeman (Global Change Biology, 2018)
Animal populations have undergone substantial declines in recent decades. These declines have occurred alongside rapid, human‐driven environmental change, including climate warming. An association between population declines and environmental change is well established, yet there has been relatively little analysis of the importance of the rates of climate warming and its interaction with conversion to anthropogenic land use in causing population declines. Here we present a global assessment of the impact of rapid climate warming and anthropogenic land use conversion on 987 populations of 481 species of terrestrial birds and mammals since 1950. We collated spatially referenced population trends of at least 5 years’ duration from the Living Planet database and used mixed effects models to assess the association of these trends with observed rates of climate warming, rates of conversion to anthropogenic land use, body mass, and protected area coverage. We found that declines in population abundance for both birds and mammals are greater in areas where mean temperature has increased more rapidly, and that this effect is more pronounced for birds. However, we do not find a strong effect of conversion to anthropogenic land use, body mass, or protected area coverage. Our results identify a link between rapid warming and population declines, thus supporting the notion that rapid climate warming is a global threat to biodiversity.

Proceedings of the third international molecular pathological epidemiology (MPE) meeting - Peter T. Campbell; Timothy R. Rebbeck; Reiko Nishihara; Andrew H. Beck; Colin B. Begg; Alexei A. Bogdanov; Yin Cao; Helen G. Coleman; Gordon J. Freeman; Yujing J. Heng; Curtis Huttenhower; Rafael A. Irizarry; et al. (Cancer Causes & Control, 2017)

Foraging flexibility and search patterns are unlinked during breeding in a free-ranging seabird - Akiko Shoji; Stéphane Aris-Brosou; Ellie Owen; Mark Bolton; Dave Boyle; Annette Fayet; Ben Dean; Holly Kirk; Robin Freeman; Chris Perrins; Tim Guilford (Marine Biology, 2016)

Flexible foraging strategies in a diving seabird with high flight cost - Akiko Shoji; Ellie Owen; Mark Bolton; Ben Dean; Holly Kirk; Annette Fayet; Dave Boyle; Robin Freeman; Chris Perrins; Stéphane Aris-Brosou; Tim Guilford (Marine Biology, 2014)

CYP3A4-V and prostate cancer in African Americans: causal or confounding association because of population stratification? - Rick A. Kittles; Weidong Chen; Ramesh K. Panguluri; Chiledum Ahaghotu; Aaron Jackson; Clement A. Adebamowo; Robin Griffin; Tyisha Williams; Flora Ukoli; Lucile Adams-Campbell; John Kwagyan; William Isaacs; et al. (Human Genetics, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)